Productivity growth prospects and the new economy in historical perspective - Paul David (EIB Papers, 2001)
Today there are many questions about the nature and the future of the so-called 'new economy'. The term 'new economy' itself has acquired a variety of quite different connotations. For many commentators, it continues to refer primarily to the altered macroeconomic performance of the US economy during the 1990s, when an accelerating rate of growth of real GDP and a steadily falling unemployment rate, unexpectedly, did not give rise to inflationary pressures on wages and prices. Some connected this with evidence of the revival of labour productivity growth, which became increasingly visible in the aggregate statistics for the private sector, as the key development heralding an escape from the US economys puzzling and worrisomely poor productivity performance of the preceding two decades.
Keywords: 330; Produktivität; Wirtschaftswachstum; Welt; New Economy